METHODS OF PERFORMANCE ANALYSIS IN BANKS - BATRANCEA IOAN; GABAN LUCIAN; RUS IONUT; MINTEUAN PAUL (Annals of the University of Oradea: Economic Science, 2016)
Performance generally in the banking specifically highlight on the one hand the financial institution's ability to generate profit, and on the other hand shows the consequences of financial decisions taken by the bank's management. In our opinion bank decisions are based on the analysis of the effects of the bank's policy in the past period. Therefore the paper presents such an analysis that supports decision makers banking.